Inequality of personal income in the enlarged EU: The role of the welfare states, regional cohesion policies and economic integration - Onno Hoffmeister (Luxembourg Income Study (LIS), 2006)
This study examines how the distribution of income across persons, regions, countries and larger geographical areas in the EU has changed in the dawn of the enlargement of the EU. It focuses especially on the effects of trade liberalization, the welfare states and the regional cohesion policy implemented at the European level. Moreover, it assesses the statistical effect resulting from the enlargement of the community of people for which inequality is to be measured. A three-level spatial decomposition of personal inequality reveals that a fifth of the overall interpersonal inequality in the EU is attributed to the East-West income gap and that intra-regional inequality accounts for three quarters of the overall inequality. Within-country personal inequality shows a clear convergence throughout the member states: Inequality is rising in the Scandinavian social-democratic welfare states and de-creasing in the liberal and Mediterranean countries. In Central Eastern Europe, the rapid growth of inequality which had been observable during the first years of transition has come to an end.
Keywords: 330; EU-Mitgliedschaft; Regionale Einkommensverteilung; Einkommensverteilung; Handelsliberalisierung; EU-Regionalpolitik; Sozialstaat; EU-Staaten